Dynamic Capabilities, Knowledge Sharing, and Environmental Dynamism: A Mediated–Moderation Model of SME Innovation Performance - Yuli Budiati; Hardani Widhiastuti; Indarto Indarto; Rohmini Indah Lestari (Annals of Management and Organization Research, 2026)
Purpose: This study examines the relationship between dynamic capabilities and innovation performance in Small and Medium-sized Enterprises (SMEs), with knowledge sharing as a mediator and environmental dynamism as a moderator. Methodology: This study used a quantitative survey of 194 SMEs in Central Java. Data were collected using structured questionnaires, purposive sampling, and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. Results: Dynamic capabilities substantially impact innovation performance and knowledge sharing. Knowledge sharing positively influences innovation performance and mediates the effect of dynamic capabilities on it. Environmental dynamism directly and positively influences innovation performance but does not significantly strengthen the relationship between dynamic capabilities and innovation performance. Conclusions: Dynamic capabilities improve innovation performance directly and indirectly through knowledge sharing.  Internal capabilities play a more dominant role than external environmental conditions in driving innovation. Limitations:  This study is limited by its cross-sectional design and moderate explanatory power, indicating the possible influence of other variables. Contributions:  This study addresses gaps in the dynamic capability and knowledge-based view literature through evidence from SMEs in developing countries and offers practical insights for managers to enhance innovation through capability development and knowledge sharing.